2013
DOI: 10.12816/0003278
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Induced Acute Dystonic Reactions after a Standard Therapeutic Dose for Uncomplicated Malaria = تفاعل خلل التوتر العضلي الحاد بعد جرعة قياسية للكلوروكين لعلاج الملاريا غير المعقدة

Abstract: Acute dystonic reactions (ADR) are extrapyramidal effects that usually occur after the initiation of a wide variety of drugs or triggering factors besides neuroleptics. We report the case of a 54-year-old man who was admitted with an approximately 10-hour history of muscle twitching around the eyes, face and neck after he took the first dose of oral chloroquine phosphate (1 g [600 mg base]) prescribed for uncomplicated malaria. He was given intravenous diazepam (10 mg statum) followed by 10 mg of oral diazepam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…43 Another report revealed that extrapyramidal syndrome might also occur after the administration of a single standard dose of CQ. 44 Hallucination and Psychosis Previous studies revealed that CQ could induce psychotic features such as mood disorder (mixed episode), irritability, anxiousness, agitation, and blunted mood. These psychotic features were more common accompanied by positive symptoms, hallucination, and derealization.…”
Section: Major Neurologic Adverse Drug Reactions (Adrs)mentioning
confidence: 99%
“…43 Another report revealed that extrapyramidal syndrome might also occur after the administration of a single standard dose of CQ. 44 Hallucination and Psychosis Previous studies revealed that CQ could induce psychotic features such as mood disorder (mixed episode), irritability, anxiousness, agitation, and blunted mood. These psychotic features were more common accompanied by positive symptoms, hallucination, and derealization.…”
Section: Major Neurologic Adverse Drug Reactions (Adrs)mentioning
confidence: 99%
“…Medication-induced acute dystonia can be a side effect of treatment with antiemetics, antipsychotics, antidepressants, antiepileptics, antimalarials, and other drugs 7,8. Such drugs produce acute dystonic reactions through a nigrostriatal dopamine D2 receptor blockade, which results in an excess of striatal cholinergic output 9. These drug-induced side effects are dose independent 8.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Such drugs produce acute dystonic reactions through a nigrostriatal dopamine D2 receptor blockade, which results in an excess of striatal cholinergic output. 9 These drug-induced side effects are dose independent. 8 Metoclopramide, the most commonly prescribed antiemetic, may cause acute dystonic reactions at any age even if it is used at therapeutic dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Auch reversible extrapyramidale Störungen (z. B. Dyskinesien, Dystonien, Tremor, Parkinsonismus [47,[60][61][62][63]), Hörstörungen [48] und hirnorganische Psychosen [47,48] kommen selten vor. Die Häufigkeit neurologischer Komplikationen soll bei 5 % liegen [48].…”
Section: Chloroquin Und Hydroxychloroquinunclassified